2006
DOI: 10.1159/000094492
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in Rat Liver Cirrhosis: Blockade of Tumor Necrosis Factor-α via Inhibition of Degradation of an Inhibitor of Nuclear Factor-κB

Abstract: Background/Aims: Thalidomide inhibited tumor necrosis factor-α (TNF-α) effectively in many trials. The aim of this study was to investigate the effect of thalidomide on the expression of nuclear factor-ĸB (NF-ĸB), inhibitor of NF-ĸB (IĸB) and TNF-α in a rat model of liver cirrhosis. Methods: Liver cirrhosis was achieved by intraperitoneal injection of carbon tetrachloride thrice weekly, and thalidomide (10 or 100 mg/kg/day) was given daily by intragastric route for 8 weeks. Serum alanine aminotransferase (ALT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 92 publications
1
13
0
Order By: Relevance
“…Previous studies also demonstrated that thalidomide has inhibitory effects on TNF-α secretion by unstimulated peripheral blood cells treated for two days [13]. Thalidomide may curtail TNF-α production by inhibiting degradation of the inhibitor of kappa B (IκB) and thus, NF-κB-mediated expression of TNF-α mRNA [24]. Here, we also detected downregulation of TNF-α production by LPS-stimulated MΦ after thalidomide treatment.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies also demonstrated that thalidomide has inhibitory effects on TNF-α secretion by unstimulated peripheral blood cells treated for two days [13]. Thalidomide may curtail TNF-α production by inhibiting degradation of the inhibitor of kappa B (IκB) and thus, NF-κB-mediated expression of TNF-α mRNA [24]. Here, we also detected downregulation of TNF-α production by LPS-stimulated MΦ after thalidomide treatment.…”
Section: Discussionsupporting
confidence: 73%
“…[32][33][34][35][36] Suppression of NF-κB activation may represent a target for the prevention and treatment of liver fibrosis. 32,36) It has been generally accepted that the expression of α-SMA in HSCs increases in CCl 4 -induced acute liver injury. 35,37,38) In this study, gomisin A inhibited the increase in the hepatic mRNA and protein levels of α-SMA.…”
Section: Discussionmentioning
confidence: 99%
“…8 Therefore, the effect of thalidomide on LPS-induced NF-kB activation was examined in RAW 264.7 cells (Fig. 2).…”
Section: Thalidomide Inhibits the Activation Of Nf-kb In Lps-stimulatmentioning
confidence: 99%